The Validation Of Chemical And Immunological Tests For Antimalarials In Body Fluids: Papers Presented At A Who/Universiti Sains Malaysia Workshop. - Navaratnam, Profesor Madya (Dr.) V.; Payne, Dr. D. (Pusat Penyelidikan Dadah Dan Ubat-Ubatan Universiti Sains Malaysia, 1990)

(untitled)
Following the recommendations of the Workshop on Clinical Pharmacology of Antimalarial Drugs, which was held in Penang from 23 January to 4 February, 1989, the steering committee of CHEMAL, UNDP/World Bank/WHO special Programme of Research and Training in Tropical Diseases (TOR), authorized the organisation of a follow-up Workshop on Chemical and Immunological Tests for Antimalarials in Body Fluids.